2019
DOI: 10.3390/antiox8110541
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Bioactive Phenanthrenes in Dioscorea batatas Decne Peel, a Discarded Biomass from Postharvest Processing

Abstract: Dioscorea batatas Decne (Chinese yam) has been widely cultivated in East Asia for the purposes of food and medicinal uses for centuries. Along with its high nutritional value, the medicinal value of D. batatas has been extensively investigated in association with phytochemicals such as allantoin, flavonoids, saponins and phenanthrenes. Phenanthrenes are especially considered the standard marker chemicals of the Chinese yam for their potent bioactivity and availability of analysis with conventional high perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
0
20
1
Order By: Relevance
“…Dioscorea (yam) species, comprising approximately 600 variants worldwide, are consumed as an edible root vegetable [ 1 ]. Yam species have high nutritional and pharmacological value because they contain polysaccharides, steroidal saponins, allantoin, and polyphenols, such as flavonoids [ 2 ]. A number of recent studies have demonstrated that yam roots exhibit various biological and pharmacological activities, such as antioxidant, cholesterol-lowering, growth hormone releasing, and anti-inflammatory, as well as show protective effects against ethanol-induced gastric ulcers [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dioscorea (yam) species, comprising approximately 600 variants worldwide, are consumed as an edible root vegetable [ 1 ]. Yam species have high nutritional and pharmacological value because they contain polysaccharides, steroidal saponins, allantoin, and polyphenols, such as flavonoids [ 2 ]. A number of recent studies have demonstrated that yam roots exhibit various biological and pharmacological activities, such as antioxidant, cholesterol-lowering, growth hormone releasing, and anti-inflammatory, as well as show protective effects against ethanol-induced gastric ulcers [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that allantoin, which is found in plants like chamomile, wheat sprouts, sugar beet, and comfrey, has been widely used in anti-aging serum [ 85 , 86 ]. Allantoin is also a well-known anti-irritating and hydrating agent as well as a peeling agent for skin [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mitochondrial DNA mutations (mtDNA) contribute to more than 5% of post-lingual non-syndromic hearing impairment in the Caucasian and Asian populations 5 , 6 . Mutations in the mtDNA or nuclear DNA, which affect mitochondrial function, could result in increased oxidative damage and associated loss of HCs, SGNs, or cells of stria vascularis 7 , 8 . Like in many other cell types in an organism, mitochondria in the cochlear cells are responsible for vital cellular functions, including energy production, apoptosis, cell signaling, and calcium storage.…”
Section: Introductionmentioning
confidence: 99%